Structural Vulnerability and Sectoral Interdependence Embodied in Global Nickel Ore Flows from Source to Sink - Liu, Yihong; Chen, Jinpu; Li, Xiao; Gill, Muhammad Yasin; Qadeer, Shazia; Fan, Ying; Li, Zhi; Chen, Guoqian (Journal of Environmental Accounting and Management, 2026)
Nickel ore has emerged as a strategic mineral for decarbonizing the global economy through transport electrification. However, prevailing assessments overlook intricate interdependencies that underpin global nickel supply chains. Here, we introduce Environmental Extended Input-Output Analysis (EEIOA) to construct a consumption-based framework for tracing nickel flows at regional and sectoral resolution in 2022, and evaluate the supply security via self-sufficiency rates. Our findings reveal a profound geographical asymmetry between extraction and final use, inducing structurally different trade patterns. Physical trade exhibits a concentration and transfers nickel ores from mining areas to manufacturing hubs, while embodied trade demonstrates a decentration pattern. This is driven by the disparity of final use, characterized by a stark contrast between China and Indonesia, the top two users. The final use of China is structurally locked into investment-led demand and dependent on the construction sector, contributing 84.8% of nickel utility in fixed capital formation. Despite domestic extraction, China faces a structural vulnerability with a self-sufficiency rate of only 24.9% due to the greatest domestic demand. Conversely, Indonesia’s nickel utility is primarily consumed by households and supported by transportation and public service sectors, with a self-sufficiency rate of 97.9%. These results provide a systemic insight into vulnerabilities of nickel supply chains and an analytical benchmark for fairness and security in resource governance.